2020
DOI: 10.3390/atmos11080813
|View full text |Cite
|
Sign up to set email alerts
|

Updated Assessment of Temperature Extremes over the Middle East–North Africa (MENA) Region from Observational and CMIP5 Data

Abstract: The objective of this analysis is to provide an up-to-date observation-based assessment of the evolution of temperature extremes in the Middle East–North Africa (MENA) region and evaluate the performance of global climate model simulations of the past four decades. A list of indices of temperature extremes, based on absolute level, threshold, percentile and duration is used, as defined by the Expert Team on Climate Change Detection and Indices (ETCCDI). We use daily near-surface air temperature (Tmax and Tmin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The indices are easy to interpret, give robust results therefore they have many applications in climate research and other related areas [2]. They have been used to investigate and monitor global changes in extreme events with observational data [9,10,13,14], with projected future data [2,11,[15][16][17] or to evaluate model performance [12,18]. The indices also enable regional analyses of extreme event changes therefore model performance evaluated also regionally [19] and the regional changes in temperature and precipitation extreme events have been assessed for many parts of the world during the recent decades, such as in Australia [20], North America [21,22], the United States [23], the Mediterranean Basin [24], countries of Western Indian Ocean [25], the Arab Region [26], China [5,27,28], Iran [29], Egypt [30], Central and South Asia [31], East Asia [32], Ethiopia [33][34][35], Saudi Arabia [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indices are easy to interpret, give robust results therefore they have many applications in climate research and other related areas [2]. They have been used to investigate and monitor global changes in extreme events with observational data [9,10,13,14], with projected future data [2,11,[15][16][17] or to evaluate model performance [12,18]. The indices also enable regional analyses of extreme event changes therefore model performance evaluated also regionally [19] and the regional changes in temperature and precipitation extreme events have been assessed for many parts of the world during the recent decades, such as in Australia [20], North America [21,22], the United States [23], the Mediterranean Basin [24], countries of Western Indian Ocean [25], the Arab Region [26], China [5,27,28], Iran [29], Egypt [30], Central and South Asia [31], East Asia [32], Ethiopia [33][34][35], Saudi Arabia [36].…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary study to the work of Sillmann et al [2], the aim of this study is to investigate the projected changes in climate extreme indices defined by ETCCDI over Coordinated Regional Climate Downscaling Experiment (CORDEX) Region 13 that is Middle East and North Africa (MENA) for the end of the 21st century. The primary tools for studying possible future changes in climate mean, variability and climate extremes are the simulations with global coupled ocean-atmosphere general circulation models (CGCMs) [11,14]. Since the CGCMs have coarse resolution (100-300 km) and they have no topographic information at finer scales, they are not suitable for generating detailed results [46].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, many studies have reported an increase in temperature period indices and a decrease in cold and frost indices using CMIP5 models. Examples include research in the United States (Barnett et al 2012), Mainland China (Ying et al 2020), South Asia (Ullah et al 2020), and the Middle East -North Africa (MENA) (Ntoumos et al 2020). Therefore, it can be acknowledged that global warming in Iran will be very intense in the coming years and this increasing intensity will be signi cant for indices related to duration.…”
Section: The Seasonal Anomaly Of Extreme Temperature Indices (Eti) In Iranmentioning
confidence: 99%
“…Globally, many studies have reported an increase in temperature period indices and a decrease in cold and frost indices using CMIP5 models. Examples include research in the United States (Barnett et al 2012) (Ntoumos et al 2020). Therefore, it can be acknowledged that global warming in Iran will be very intense in the coming years and this increasing intensity will be signi cant for indices related to duration.…”
Section: The Seasonal Anomaly Of Extreme Temperature Indices (Eti) In Iranmentioning
confidence: 99%